SERIE EDITOR: SIMON SINEK "START WITH WHY" - Ismoilova Gulyora Xabibullo qizi; Abduraxmonova Maxfiratxon Xurshidjon qizi (Journal of new century innovations, 2022)
Abstract: One of the most famous person in business industry Simon Sinek clearly shows how a true leader should be in the workplace in his book called"Start With Why". He mentions that the role of a leader is not to come up with all great ideas . The role of a leader is to create an environment in which great ideas can happen. No matter how industriousness the leader is , this is of no benefit to the organization if other members don`t know what they have to do , why they have to do and how they can do this work. So, Simon shows the importance of how, what, why in his this amazing book.